2014
DOI: 10.1017/s0033291714001020
|View full text |Cite
|
Sign up to set email alerts
|

Refining the latent structure of neuropsychological performance in schizophrenia

Abstract: Factor structures derived in the current study were broadly similar to those reported previously. However, factor structures between schizophrenia subjects and healthy controls were different. Roles of factor analytic-derived g estimands and conventional composite score g were further discussed. Cognitive structures underlying cognitive deficits in schizophrenia may prove useful for interrogating biological substrates and enriching effect sizes for subsequent work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 89 publications
(110 reference statements)
3
23
0
Order By: Relevance
“…Previous research in a large schizophrenia sample found that cognitive impairment was best explained by a single deficit factor (Keefe et al, 2006); however, this study did not include controls and so could not directly asses how patterns found in patients compare to typical cognitive structure. A model including executive functioning, memory and processing speed best discriminates schizophrenia from controls (Lam et al, 2014), which supports the theory that patients with schizophrenia are broadly cognitive impaired, but this study included relatively independent cognitive tasks and the structure within multiple memory-related tasks has not been measured. Additionally, more refined, cognitive neuroscience-based tasks might better identify discrete neurocognitive subsystems that are impaired in patient groups (Carter and Barch, 2007).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous research in a large schizophrenia sample found that cognitive impairment was best explained by a single deficit factor (Keefe et al, 2006); however, this study did not include controls and so could not directly asses how patterns found in patients compare to typical cognitive structure. A model including executive functioning, memory and processing speed best discriminates schizophrenia from controls (Lam et al, 2014), which supports the theory that patients with schizophrenia are broadly cognitive impaired, but this study included relatively independent cognitive tasks and the structure within multiple memory-related tasks has not been measured. Additionally, more refined, cognitive neuroscience-based tasks might better identify discrete neurocognitive subsystems that are impaired in patient groups (Carter and Barch, 2007).…”
Section: Introductionsupporting
confidence: 67%
“…This and the similarity to published norms (Norman et al, 2000) suggests it is unlikely that the group differences detected in this study are due to over-sampling of high functioning healthy individuals. The smaller sizes of the patient groups means that we may not have sampled the full performance distribution in the patients and may not be able to detect subtle differences in the underlying cognitive structure (Lam et al, 2014). However, our results did not differ when factor loadings were derived from controls alone.…”
Section: Discussionmentioning
confidence: 99%
“…In step two, a confirmatory factor analysis (CFA) was performed using the remaining half of each group to validate the derived model. As a secondary aim given the limited number of tests in the BACS battery, we also compared the single factor solution determined with the EFA to a model with more factors based on reports from some previous investigations about the cognitive structure of psychotic disorders (Lam et al, 2014; Keefe et al, 2004; McCleery et al, 2015). Model fit was evaluated using the following measures: Tucker-Lewis Index (TLI) (Bollen, 1989), Comparative Fit Index (CFI) (Bentler, 1990), Root Mean Square Approximation (RMSEA) (Browne & Cudeck, 1993), Akaike information criterion (AIC), Bayesian information criterion (BIC), and a Chi-square test of goodness of fit.…”
Section: Methodsmentioning
confidence: 99%
“…Neuropsychological impairment is a core feature of schizophrenia (Hill et al, 2004b; Keefe et al, 2007; Lam et al, 2014). Impairments have been reported in many cognitive domains, including verbal learning and memory, verbal fluency, working memory, processing speed, and executive function (Bilder et al, 2002; Hill et al, 2013, 2004a; Saykin et al, 1994).…”
Section: Introductionmentioning
confidence: 99%